Langkah Praktis Menuju Persaingan Bisnis yang Lebih Sehat Melalui Digitalisasi UMKM Kelurahan Benda, Kota Tangerang - Cahyani Kurniastuti; Priyo Susilo; Ismayudin Yuliyzar; Putra Pratama; Suparman Suparman (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of implementing community service in Benda sub-district is to support business actors in promoting SME products in Benda sub-district, Tangerang-Banten City. This activity began with a preparation and field survey stage, which involved direct discussions with the village administrators and village officials of Benda Subdistrict to identify the needs, opportunities and challenges faced by SME business actors. Next, the service team carries out the socialization and training stage, which includes five important aspects: (1) how to create attractive products, (2) choosing a strategic location, (3) practice of creating easy promotional content on social media, (4) distribution strategy products to reach customers, and (5) online marketing. This activity aims to produce SMEs in Benda sub-district, especially home-based businesses, who have an entrepreneurial spirit so they are able to create good marketing strategies. This research aims to optimize the application of digitalization to MSMEs in Benda Subdistrict, Tangerang City, in order to strengthen their position in increasingly dynamic business competition. Through Community Service with seminars and workshops held to provide motivation and marketing strategies as well as introduce digital technology in MSME business operations. The results show a significant increase in MSMEs' abilities and understanding of marketing strategies and the use of digital technology to face healthy competition.